STUDENTS' CREATIVE THINKING PROCESS IN SOLVING MATHEMATICS PROBLEMS ASSISTED BY CHATGPT REVIEWED FROM SELF-EFFICACY - Astin Anas; Masriyah; Abdul Haris Rosyidi (RADJA PUBLIKA, 2026)
Creative thinking is an essential component of mathematical problem solving, yet its development remains underexplored, particularly regarding how students with different self-efficacy levels engage in creative thinking processes during ChatGPT-assisted mathematical problem solving. This study aimed to describe the creative thinking processes of students with high, moderate, and low self-efficacys in solving mathematical problems assisted by ChatGPT. A descriptive qualitative approach was employed, involving three Grade XI students selected through purposive sampling to represent high, moderate, and low self-efficacys categories with equivalent mathematical abilities. Data were collected through self-efficacy questionnaires, mathematical problem-solving tasks, interviews, and then analyzed using interactive qualitative analysis with time triangulation. The results showed that students across all self-efficacy levels completed the stages of preparation, mini-incubation, illumination, and verification. However, differences emerged in their levels of independence, idea development, and depth of verification; student with high self-efficacy demonstrated more independent and reflective thinking processes than those with moderate and low self-efficacy. These findings indicate that self-efficacy influences the quality of students’ creative thinking processes when utilizing ChatGPT for mathematical problem solving.